2018
DOI: 10.1002/slct.201800338
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Composite of Biomass Porous Carbon/SnO2/Pt: An Efficient Catalyst for Reduction of Aromatic Nitro Compounds

Abstract: Ternary composite of biomass porous carbon/SnO 2 /Pt was prepared by a facile two-step method consisting of the hydrothermal process and the impregnation-chemical reduction procedure. The SEM and TEM revealed that particles of SnO 2 deposited on the surface of porous carbon (PC) and formed an intermediate layer, which facilitated Pt nanoparticles (around 3-4 nm) to deposit uniformly and firmly on the surface. The ternary composite catalyst of Pt-SnO 2 /PC exhibited significantly enhanced performance during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This phenomenon also showed that this reaction followed pseudo-first-order kinetics. From the slope of this equation, the apparent rate constant (K) for the reduction of 4-nitrophenol was obtained of 0.047 s −1 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon also showed that this reaction followed pseudo-first-order kinetics. From the slope of this equation, the apparent rate constant (K) for the reduction of 4-nitrophenol was obtained of 0.047 s −1 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic performance of Fe 3 O 4 @Pt NPs composites was initially tested by the model reaction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP), which was usually catalyzed by metal nanomaterials, as shown in Figure a. Before the addition of Fe 3 O 4 @Pt NPs, the UV–vis spectrum of the mixture aqueous solution of 4-NP and NaBH 4 showed a strong absorption peak at 400 nm, which was attributed to the formation of 4-nitrophenolate anions.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of hydrocracking reactions, such as those for treating used cooking oil, pyrolysis of fuel oil and 1-methylnaphalene into BTX chemicals, changing plastic waste into liquid fuels, and converting hexadecane to jet fuel, have been catalyzed by zeolites in recent years. Zeolite Y has been widely used in industrial applications such as hydrocracking and hydrotreating catalysts due to its high stability at high temperature, durability and activity .…”
Section: Challenges and Perspectivesmentioning
confidence: 99%